NEOGENE RADIOLARIAN BIOSTRATIGRAPHY FROM ODP LEG 119, SITE 745 - Sharma, Girish Kumar (Ofioliti, 2013)
Abundant, generally well preserved radiolarians were used in a stratigraphic analysis of the Neogene sequence of ODP Leg 119, Site 745. Detailed biostratigraphic analysis has been undertaken of radiolarian assemblages of the Pliocene-Pleistocene sequence. Seventy-seven radiolarian taxa were identified including three reworked forms. Twenty-one stratigraphically important species are described and illustrated from this 99.55 m long core, and allow the recognition of four radiolarian zones, i.e., Phi, Chi, Psi and Omega (from oldest to youngest) and the Plio-Pleistocene boundary. These are then correlated with the earlier established zones and boundary in the Southern Ocean.